PENGARUH PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Angelina, Helen; Daryanti , Sri; Simina, Juni (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to analyze the effect of profitability, liquidity, and firm size towards firm value on listed consumer cyclical companies in Indonesia Stock Exchange (IDX) from the year 2019-2021. Sample was selected by purposive sampling method and the selected data was 73 consumer cyclical companies. The data analysis method used in this study is multiple linear regression analysis to test the hypothesis and used SPSS V25 Software program and Microsoft Excel 365 to process data from this research. The results showed that profitability has no positive significant effect on firm value. However, liquidity and firm size have a negative significant effect on firm value. The implication of this research is the need of planning in increasing profitability, liquidity, and firm size in order to increase firm value.